CNS tuberculosis: diagnostic challenges and review of recent laboratory investigations - Gautam, Vinod; Gupta, Renu (International Journal of Medicine, 2017)
Tuberculosis of the central nervous system poses a diagnostic and therapeutic challenge to the physicians. Early diagnosis is warranted to reduce morbidity and mortality associated with this disease. Microbiological investigations for the diagnosis of tuberculosis of central nervous system are of paramount significance. However, due to relative inaccessibility of approaching infected lesions in eloquent area of brain and difficulty in retrieving pathological sample from deep located regions of the brain and spinal cord without causing any neurological deficit, there is need to review the relevance of available microbiological and biochemical tests. Some tests which may be very specific like AFB microscopy and culture may not be positive in many cases due to paucibacillary CSF sample or pus or granulation tissue from the brain or spine. So, authors have reviewed different biochemical and microbiological tests and suggested a pragmatic and step wise practical approach for use of laboratory investigations in clinical management of CNS TB patients.